รูปแบบทางธุรกิจของตลาดกลางอิเล็กทรอนิกส์สำหรับบริการขนส่งด้วยรถบรรทุกในประเทศไทย - ชัชสรัญ กตัญญูคุณานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
In this paper, is to study the management system related to business electronic marketplace for transport by trucks that are both domestic and foreign. We further analyze and compare the specific solution frameworks in Electronic Freight Transport Market Place Business Model to design and simulation (Modeling) a business model of electronic marketplace for the trucking service in Thailand. Results from this study showed that the success factors in the electronics market there are 15 main drivers. They are (1) Ownership (2) Bias of e-Marketplaces (3) Participants (4) Method of Trading (5) Service Focus (6) Partnerships (7) Value Offering (8) Creation of Complementary (9) Value Stream (10) Operation Cost (11) Service Charge Payer (12) Industrial Factors (13) Competitions (14) Regulations (15) Information Technology Capacity. The fifteen factors that will require an effective management mechanism will be sufficient to meet the diverse transportation market in its current customers demand diverse Also must be able to respond to uncertainties in transportation increased as well.